Estudio de pre factibilidad comercial para el cultivo de stevia dirigido al mercado externo - Beltran Vega, Lessing Hernan (2014)
The market mainly Stevia can be divided into three groups:The largest market for Stevia is currently the food industry and the beverage, mainly as a sweetener and flavoring.The healthcare market is second in order of importance.In the third, are the byproducts formed by the remains of the plant once the leaves have been selected for the tea industry or mining.The 70% of the total world production of Stevia is used to extract crystals called "stevioside" and "Rebaudósidos-A", while 30% is intended for herbal uses.One of the limitations of market growth and atonement and cultivation of Stevia is that it has always been subject to a regulatory framework and this determined their economic performance. Your marketing is more limited when it is regulated as a dietary supplement, and is larger when it is defined as a food additive, including sweeteners.Note that the food and beverage industry is one of the most regulated in the world. It is not surprising that Stevia is experiencing barriers to growth, especially as a natural sweetener certificate. The way to improve the competitiveness of Stevia is to meet the regulatory and try that countries generally allowed as a food additive and it can be used as a natural sweetener.Scientific studies support the use of Stevia are available in Japan, Brazil, Denmark and other countries. Approximately 1 500 scientific research has resulted only in Japan who have a comprehensive approach and try to use the whole plant, not only the blade, through a variety of applications affect not only the health and welfare human beings but also of animals, ecology, and soil.Therefore, these investigations are actually elements that provide competitive advantages to Asian markets by type of regulation to the product. Probably, these markets are better positioned to take advantage of the benefits of deregulation.Production of Stevia leaves and extracts has increased because Japanese regulations, which are considerably more accessible to producers of Stevia that the measures of other countries as the United States and the European Union.On the other hand, the production of Paraguay and Brazil is focused on other markets, both from Brazil, Mexico and other Latin American countries. Ideal for export markets that may be considered by Paraguay and Brazil are the United States and member countries of the European Union. Paraguay and Brazil later began commercial production of Stevia and competitive challenges faced by China for its higher transaction costs and transportation and the Chinese position in the Japanese market.Paraguayan Studies yields per hectare of dry leaf of Stevia could improve with changes in crop management, a study suggests Paraguay reach yield 3000 kg / ha. The crop can be harvested two to four times per year.